IMPLEMENTASI KURIKULUM MERDEKA (IKM) SEBAGAI SEBUAH PILIHAN BAGI SATUAN PENDIDIKAN: KAJIAN PUSTAKA - Fajrina Sulistyani; Rahmat Mulyono (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2022)
The purpose of this research is to analyze Kurikulum Merdeka as an option for a school. A school may choose the curriculum which suitable to the needs for the teachers and the students to simplify the students to learn and to make a school as a comfortable, a safe and a joyful place. The needs of a school consist of the aim, method, material and evaluation of learning for the teachers and the students. The method of this research is a qualitative research. The researcher collects the data by reading, writing and processing research material. The result of this study state that a school can choose a curriculum which will be used in the next learning year. The options are kurikulum 2013, kurikulum darurat and kurikulum merdeka. When a school choose kurikulum merdeka as their curriculum, it has an opportunity to choose Mandiri Belajar, Mandiri Berubah dan Mandiri Berbagi.